واقع إنتاج التمور وتسويقها في ليبيا: (دراسة حالة منطقة الجفرة) - عبد السلام عبد الحفيظ الصلاي (Scientific Journal of University of Benghazi, 2019)
The cultivation The current research aims to study the current status of date palm production and identify the most important problems and pests experienced by palm growers in Aljufra Municipality، in addition to adding a case study to farmers of dates in the sample of research in Aljufra area. The research was based on secondary data sources، a random sample of date palm producers in Aljufra area، 40 respondents، 4 respondents from wholesalers and 5 respondents from retailers. The linear regression method was applied in the smallest squares method. Logarithmic half image for the independent factors to estimate some factors affecting the production of dates، and found that the rate of production dates and cultivation in Libya has increased in recent years، reaching 188.6 thousand tons in 2016، compared to 85 thousand tons in 1990. The area planted with palm trees increased from 24.6 thousand hectares in 1990 to 36.5 thousand hectares in 2016. The results of the current research showed the presence of many pests and diseases that affect the palm trees in Aljufra municipality. The top of these is the green crusty insect، the dream of dust and the dopes. The incidence of these pests reached 60%. The results also showed high prices of fertilizers and pesticides، which has had a negative effect on palm productivity، and the state and its institutions have had little role to support palm farmers. The country's conflicting decisions to prevent exports and the absence of alternative channels caused 57.5% of the marketing problems. The accumulation of production and the inability of the local market to absorb 37.5% of the marketing problems، while the high prices of packing and labor and the absence of factories for date products to 5% of the marketing problems، as shown and a change of 1% in each area cultivatedX1)، and the total number of productive date palm (X3)، leading to an increase in total date production by about 11.46 and 9.92 tons.